(untitled) (Revista Posgrado y Sociedad, 2020)
The historical and cultural richness along with the diversity in natural resources in Guanacaste, Costa Rica empowers communities of this region to be an ideal place for producing educative documentaries. Recent developments in social media promotion and in electronic intelligent devices stimulate the inhabitants of that same communities to watch and enjoy this form of audiovisual research. It is necessary to promote these audiovisual productions in social networks for native people of guanacastecan towns in order to appreciate their own culture, origins and history reflected in those documentaries. Investment in social media promotion strategies should be planned within public universities as part of their extension programs. Financing these strategies should be part of the production logistics in offices dedicated to educative audiovisual production. It is also important for documentaries to become exterior windows for traditions that have been filmed and watched in other countries outside Costa Rica. There are different routes to make it possible, but a very important one is the inscription of these documentaries in international film festivals and also to participate on international movie competitions. Two examples of these documentary products are «The Lands of Princess Nandayure» and «A Festival in Liberia»; both produced by the Audiovisual Production Center of the State University of Distance Learning in Costa Rica.